2011
DOI: 10.2214/ajr.10.7292
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Twists and Turns: Part I, Gastrointestinal Tract Torsions With Pathologic Correlation

Abstract: Torsion-related ischemic pathology may involve any portion of the gastrointestinal tract from the stomach to the colon. The clinical presentation of gastrointestinal tract torsion is nonspecific, and radiologists are relied on to make this diagnosis. Recognition of the predisposing factors and imaging spectrum of gastrointestinal tract torsions is essential to help direct timely intervention in these potentially life-threatening entities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 20 publications
0
9
0
1
Order By: Relevance
“…More widely, connective tissue is strongly represented in various components of the GI apparatus , such as peritoneal ligaments, gut wall and splanchnic vessels. Peritoneal ligamentous laxity leading to hypermobility of the intra‐abdominal viscera is considered a predisposing factor to abdominal twists and torsions [Timpone et al, ], and could facilitate visceral prolapse or hernias under the additive effect of orthostatism and other factors increasing intra‐abdominal pressure (such as, pregnancy and chronic constipation). Accordingly, Curci et al [] found subtle alterations of the elastic fibers in the supporting ligaments of the gastro‐esophageal junction in patients with gastro‐esophageal reflux and hiatus hernia.…”
Section: Discussionmentioning
confidence: 99%
“…More widely, connective tissue is strongly represented in various components of the GI apparatus , such as peritoneal ligaments, gut wall and splanchnic vessels. Peritoneal ligamentous laxity leading to hypermobility of the intra‐abdominal viscera is considered a predisposing factor to abdominal twists and torsions [Timpone et al, ], and could facilitate visceral prolapse or hernias under the additive effect of orthostatism and other factors increasing intra‐abdominal pressure (such as, pregnancy and chronic constipation). Accordingly, Curci et al [] found subtle alterations of the elastic fibers in the supporting ligaments of the gastro‐esophageal junction in patients with gastro‐esophageal reflux and hiatus hernia.…”
Section: Discussionmentioning
confidence: 99%
“…Primary volvulus occurs in an otherwise normal abdomen; proposed risk factors include high fiber diets and altered gastrointestinal motility . Secondary volvulus occurs as a result of a preexisting factor or condition, including causes such as adhesions, congenital abnormalities (including malrotation), hernia, pregnancy, and previous surgery . In dogs, volvulus has been reported to affect the small and large intestine although both conditions are considered rare .…”
Section: Discussionmentioning
confidence: 99%
“…13 In human medicine, torsion-related ischemia is also common and may involve any portion of the gastrointestinal tract from the stomach to the colon. 14 In contrast, urinary bladder torsion rarely occurs in veterinary and human medicine and is characterized by rotation of the organ, usually at the level of the trigone, with subsequent obstruction of urine outflow. In the only reported case in human medicine, urinary bladder torsion was associated with scrotal herniation of the bladder apex.…”
Section: Discussionmentioning
confidence: 99%